PROBIOTICS AS TREATMENT OF ACUTE DIARRHEA IN INFANT AND CHILDREN - Wawan, I Wayan (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Diarrhea is a common disease in children after acute respiratory tract infection. Expected, diarrhea was found approximately one billion cases per year and the first etiology of morbidity and mortality in children in Asia, Africa, and America Latin. The management of acute diarrhea according to WHO recommendation consisted of oral rehydration (low osmolarity ORS), diet, zinc supplementation, selective antibiotic, and education to parents. In several randomized controlled trials (RCT) and meta-analysis was showing that probiotics effective for primary and secondary prevention of acute diarrhea.     st1\:*{behavior:url(#ieooui) } /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Acute Diarrhea, Child, Probiotics